The Analysis of the Effect of Land Area on Tobacco Production in Temanggung Regency - Nurul Infitah; Wahyu Lestari; Riezky Alviansyah (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
Temanggung Regency is the largest and best tobacco producer in Indonesia. Temanggung Regency is the leading supplier of the largest cigarette factories in Indonesia, namely PT Djarum and PT Gudang Garam. The existence of production factors determines the results of tobacco production. One of them is the availability of land that supports tobacco production. This research aimed to examine the effect of land area on tobacco production in Temanggung Regency. All the population was sampled in this study. The sample was 20 tobacco-producing districts in Temanggung Regency. The study was conducted in January 2020. The variable land area was used to ascertain how much tobacco is produced in Temanggung Regency as a result of—a quantitative descriptive method with secondary data from the Central Bureau of Statistics of Temanggung Regency. The population of this research is all sub-districts in Temanggung Regency. The data is time series data about the total land area, and tobacco production results from 2010-2019. Analysis of the data used is simple linear regression. The findings demonstrated that the land area had a positive effect of 48.3% on tobacco production in Temanggung Regency, while the 51.7% is affected by other variables not examined in this study. This study concludes that land area significantly affects tobacco production in Temanggung Regency.